Foraging tourism: critical moments in sustainable consumption. Issue 4 (3rd April 2018) - de Jong, Anna; Varley, Peter
ABSTRACT: Despite the prevalence of sustainability discourses across the Global North, for the majority of people abstract issues of sustainability often have a low salience with the realities of travel choices. Researchers examining sustainable tourism recognise that any changes resulting in sustainable performance are likely to come about as a result of shifts in everyday highly routinised social practices, relations and socio-technical structures. Attending to these debates, this paper examines relations between social practice, sustainability and tourism through the rise in foraging tourism in the United Kingdom. Using evidence from interviews and media analysis detailing perspectives of foraging course leaders and attendees, alongside participant observation, the paper records the ways in which foraging experiences are negotiated and accomplished in commercial contexts and what participants "do" with the ideas and practices post-experience. By engaging with debates surrounding the meanings of sustainable tourism, the paper extends understanding of these concepts through the identification of foraging tourism as a facilitator in rethinking everyday practice and discourse. The paper ends by evaluating the potentials of tourism in facilitating sustainable performance and discourse.